Masa Depan Manajemen Keuangan Digital - Marichicha Puicha L Sianturi; Aji Rahmansyah; Dadin Tajudin; Agus Salahudi; Reza Muhammad; Salsabila Esa Utami; Masno Marjohan (Lembaga Pengembangan Kinerja Dosen, 2025)
In the last two decades, the world has witnessed a digital transformation that is still taking place in various areas of life, and the financial sector is one of the most significantly affected. Financial management as a discipline and professional practice basically aims to manage financial resources effectively and efficiently to achieve organizational goals. Data security and privacy are crucial issues, especially with the increasing cyber attacks on the financial system. The method used in this research activity uses a qualitative approach method where this approach explores and understands the meaning of some individuals or groups of people who come from social problems. The scope of digital financial management is the entire financial management activity that involves the use of information technology as the main tool in the planning, budgeting, reporting, auditing, and financial decision-making processes. The main goal of financial management, including in the digital context, remains consistency, namely financial performance for organizational value. In commercial companies, this means maximizing shareholder wealth or company value in a sustainable manner. The future of digital financial management in Indonesia promises an increasingly profound transformation in the way individuals, businesses, and governments manage finances. Digitalization has been shown to increase process efficiency, expand access to services, and create innovative opportunities in the financial sector. Overall, the future of digital financial management in Indonesia is more sophisticated as new technologies will continue to be adopted – AI.